Hallazgo de pelliciera rhizophorae triana and amp; planchon (theaceae) en la costa del atlántico, con observaciones taxonómicas y biogeográficas preliminares (1982)
Pelliciera rhizopharae Triana and amp; Planchon es reported for the first time in the Atlantic Coast. This species has been considered so far as an endemics in the tropical American Pacific coast. Some biogeographical and taxonomic observations are included, as well as a description of the material found.